Factors influencing Generation Y students’ satisfaction with university websites (Acta Universitatis Danubius. Œconomica, 2020)
In the new digital era, one of the major strategic priorities for many universities is having a high quality and efficient website. While universities invest considerable resources in this domain, students may not fully realise the value or level of satisfaction they expect from a university website. As such, the purpose of this study was to explore the factors that influence Generation Y students’ satisfaction with university websites. A single cross-sectional and descriptive research design was followed in this study. A self-administered questionnaire was designed to collect data from a convenience sample of 319 Generation Y students registered at two Gauteng-based South African HEI campuses. The methods used to analyse the data included descriptive statistics, reliability and validity analysis, Pearson’s product-moment correlation analysis, collinearity diagnostics and structural equation modelling. The findings of the study suggest that information quality of university websites has a significant positive influence on the usefulness of university websites, while the system quality of university websites has a significant positive influence on the ease of use of university websites. Furthermore, the usefulness and ease of use of university websites have a significant positive influence on Generation Y students’ satisfaction with university websites. Understanding the factors that influence Generation Y students’ satisfaction with university websites, universities can formulate effective strategies that will ensure increased user satisfaction with the website, thereby recouping costs associated with developing and maintaining the website and ensuring an appropriate return in terms of increased user numbers and value.